Web 2.0 Tools in Teaching-Learning of Languages in an Inclusive Environment - Khan, Aerum (JOURNAL OF INDIAN EDUCATION, 2015)
Web 2.0 tools are web base utilities and technology tools provided by the social media, which focus on the collaborative, user driven content creation and applications leading to a more socially connected web. This idea behind creating web 2.0 tools was to get active contribution of people in creating content on the internet, rather than just accessing and consuming the content available on the web as passive users. Web 2.0 tools can be used by the educators to involve the students and enhance their essential skills like creativity, communication, language comprehension, literacy of media, technological proficiency, awareness towards global initiatives, etc. Few examples of web 2.0 tools include wikis, blogs, vodcasts, podcasts, webinars, e-mail groups, social bookmarking, web forums, instant messaging, virtual learning environment, e-portfolio, web based shared calendar, etc. In addition to these, there are specific web tools which are used for language learning like LinguaSubtitle, Babbel, Lingro, Typeit, Grammar-multi, etc. Also, there are various audio editing tools freely available which can be used for creating content which can be accessed by the differently abled audience. Some of them include Audacity software, Audio expert, Before you know it, UJAM, etc. The present paper is an exploration of various web 2.0 tools which can be used for multiple educational purposes by the teaching-learning community. While exploring these, the paper covers in detail the tools for language comprehension and adaptability, online storage and sharing, etc.